ABREVIASI BAHASA INDONESIA DALAM HARIAN JAMBI EKSPRES ONLINE - Musawwir Musawwir; Puji Tri Aryanti (Universitas Labuhanbatu, 2022)
AbstractThis study was conducted to describe the type of abbreviation, describe the origin of the abbreviation, and explain the process of abbreviation in the Jambi Ekspres Online daily. The object of this research is all the words contained in the daily rubric of Jambi Ekspres Online. Data collection is done by documentation technique. Based on the results of the study, it can be concluded that there are five types of abbreviations, namely abbreviations, acronyms, contractions, fragments, and letter symbols. There are three forms of abbreviation origin, namely words, personal names and noun phrases. Abbreviation process found as many as three processes, namely preservation of letters with six variants in the form of preservation of the first letter of each component, preservation of the first letter by eliminating conjunctions, preservation of the first letter and the last diphthong, preservation of the first letter with numbers when repeated, perpetuation of various letters that are difficult to formulate, preservation of the first letter of the compound component.Keywords: abbreviation, original form, abbreviation process.AbstrakPenelitian ini dilakukan untuk mendeskripsikan jenis abreviasi, mendeskripsikan bentuk asal abreviasi, dan menjelaskan proses abreviasi dalam harian Jambi Ekspres Online. Objek penelitian ini adalah semua kata yang terdapat dalam rubrik harian Jambi Ekspres Online. Pengumpulan data dilakukan dengan teknik dokumentasi. Berdasarkan hasil penelitian dapat disimpulkan bahwa jenis abreviasi terdapat lima bentuk, yaitu singkatan, akronim, kontraksi, penggalan, dan lambang huruf. Bentuk asal abreviasi yang ditemukan sebanyak tiga bentuk, yaitu kata, nama diri dan frasa nomina. Proses abreviasi yang ditemukan sebanyak tiga proses, yaitu pengekalan huruf dengan enam varian berupa pengekalan pengekalan huruf pertama tiap komponen, pengekalan huruf pertama dengan pelesapan konjungsi, pengekalan huruf pertama dan diftong terakhir, pengekalan huruf pertama dengan bilangan bila berulang, pengekalan berbagai huruf yang sukar dirumuskan, pengekalan huruf pertama dari komponen gabungan.